2003
DOI: 10.1016/s1388-9842(03)00152-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute afterload change on systolic ventricular function in conscious dogs with normal vs. failing hearts

Abstract: Background: To date, no data exist on the linearity and, therefore, the usefulness of the preload recruitable stroke work (PRSW) and end-systolic pressure-volume (ESPVR) relationships during acute afterload changes in heart failure. Aims: Our aim was, therefore, to characterize both relationships in a model of ventricular pacing induced heart failure at baseline and during acute changes in afterload. Methods: Dynamic left ventricular volume and transmural pressure were measured in 10 conscious dogs using sonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Previous work has shown that analysis of the time‐varying ratio of instantaneous pressure (P) to volume (V) obtained from an indwelling conductance catheter yields accurate assessment of intrinsic ventricular diastolic and systolic properties independently of loading conditions (7, 8). Therefore, dynamic PV loop analysis has been considered the gold standard in assessment of cardiac conditions (9, 10). Several load‐independent indices obtained from PV measurements are commonly used to evaluate contractility of the left ventricle (LV), including slope of the end‐systolic PV relationship, slope of the maximum first derivative of LV pressure (dP/d t max ), and preload‐recruitable stroke work (11–13).…”
mentioning
confidence: 99%
“…Previous work has shown that analysis of the time‐varying ratio of instantaneous pressure (P) to volume (V) obtained from an indwelling conductance catheter yields accurate assessment of intrinsic ventricular diastolic and systolic properties independently of loading conditions (7, 8). Therefore, dynamic PV loop analysis has been considered the gold standard in assessment of cardiac conditions (9, 10). Several load‐independent indices obtained from PV measurements are commonly used to evaluate contractility of the left ventricle (LV), including slope of the end‐systolic PV relationship, slope of the maximum first derivative of LV pressure (dP/d t max ), and preload‐recruitable stroke work (11–13).…”
mentioning
confidence: 99%
“…Moreover, a recent cardiogenic shock paradigm suggested that severe impairments in cardiac function may be associated with systemic inflammation and thus with a certain degree of vasodilatation [6]. Inopressors might, in turn, alter peripheral microcirculation [3], increase left ventricular afterload [4] and thus alter organ perfusion. We used the data from 3 different observational cohorts (ALARM-HF [8], EFICA [7] and AHEAD [12]) and compared inopressors alone to a combination of inopressors plus inodilators.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive vasoconstriction may, in turn, impair macro-hemodynamics by increasing left ventricular afterload [4], [20] and promoting myocardial oxygen delivery/oxygen consumption imbalance [21]. Catecholamines have been advocated to affect the restoration of cardiac function and increase short- and long-term mortalities [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E es revealed by an afterload increment in stunned hearts can be an unmasking of cardiac failure with concomitant excessive afterload dependence. Whether the failing myocardium in fact is excessively afterload dependent or not is somewhat controversial (10), but most studies will indicate such an afterload sensitivity (32,33).…”
Section: Discussionmentioning
confidence: 99%